AKTUALISASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN MODEL REFLEKTIF PADA MATA KULIAH AL-QUR’AN HADITS DAN PEMBELAJARANNYA - DEMINA DEMINA (Ta'dib, 2013)
Nowadays, lack of responsibility, uninterest of learning and other bad habits among the students had became real problem that was needed to be solved. Reflective Model was one solution to actualize character education where the students could understand and gain the materials given by a teacher. This research was done to the students of State College Islamic Studies (STAIN) Batusangkar who were registered in 2012/2013 academic year. The design of the research was Classroom Action Research. The result of the reseach showed that actualizing character education through Reflective Model tended to be appropriate for students to change their bad habits to be good personality.Kata kunci: aktualisasi, pendidikan karakter, pembelajaran model nreflektif, Al-Qur’an Hadits